Semi-Active Secondary Suspension Control Using Fuzzy Skyhook For Improving Railway Vehicle Dynamics Performance In Lateral Direction - Mohamad Hafiz, Harun; Mohd Razali, Md Yunos; Mohamad Zaharudin, Sariman; Fauzi, Ahmad; Khisbullah, Hudha; Rosli, Abu Bakar (Asian Research Publishing Network (ARPN), 2016)
In railway vehicle technology, there are continuously increasing requirements regarding riding comfort, running safety, and speed of railway vehicles. These requirements are opposed by the fact that the condition of the tracks is getting worse and maintenance is becoming expensive. In view of this conflict, conventional suspension concepts are unable to accommodate those needs. This paper investigates the performance of semi-active control of lateral suspension system namely fuzzy body-based skyhook and fuzzy bogie-based skyhook for the purpose of attenuating the effects of track irregularities to the body lateral displacement, body roll angle and unwanted yaw responses of railway vehicle. In fuzzy bogie-based skyhook, a virtual damper is attached between bogie and sky to damp out unwanted vibratory motion of the bogie and to prevent the motion to be transmitted to the body. For fuzzy body-based skyhook, the virtual damper is attached between the body and the sky. The controller is optimized on 17-DOF railway vehicle dynamics model and shown 35 % better dynamics performance than its counterparts.